The Poverty Implications of Alternative Tax Reforms : Results from a Numerical Application to Pakistan - Feltenstein, Andrew; Mejia-Mantilla, Carolina; Newhouse, David; Sedrakyan, Gohar (World Bank, Washington, DC, 2017)
This paper presents results from four simulations of the impact of potential tax reforms in Pakistan on poverty, shared prosperity, and inequality. The simulations are carried out in the context of a dynamic computational general equilibrium model that incorporates endogenous tax evasion. The simulations link the computational general equilibrium model to household survey data that are incorporated in a micro simulation model. The combined models suggest that equal yield increases in sales and corporate tax rates differ mildly in their impacts on consumption and poverty. Endogenously modeled tax evasion plays an important role in the results.